Alpha and broadband high‐frequency activity track task dynamics and predict performance in controlled decision‐making. (20th July 2021) - Haegens, Saskia; Pathak, Yagna J.; Smith, Elliot H.; Mikell, Charles B.; Banks, Garrett P.; Yates, Mark; Bijanki, Kelly R.; Schevon, Catherine A.; McKhann, Guy M.; Schroeder, Charles E.; Sheth, Sameer A.
Abstract: Intracranial recordings in human subjects provide a unique, fine‐grained temporal and spatial resolution inaccessible to conventional non‐invasive methods. A prominent signal in these recordings is broadband high‐frequency activity (approx. 70–150 Hz), generally considered to reflect neuronal excitation. Here we explored the use of this broadband signal to track, on a single‐trial basis, the temporal and spatial distribution of task‐engaged areas involved in decision‐making. We additionally focused on the alpha rhythm (8–14 Hz), thought to regulate the (dis)engagement of neuronal populations based on task demands. Using these signals, we characterized activity across cortex using intracranial recordings in patients with intractable epilepsy performing the Multi‐Source Interference Task, a Stroop‐like decision‐making paradigm. We analyzed recordings both from grid electrodes placed over cortical areas including frontotemporal and parietal cortex, and depth electrodes in prefrontal regions, including cingulate cortex. We found a widespread negative relationship between alpha power and broadband activity, substantiating the gating role of alpha in regions beyond sensory/motor cortex. Combined, these signals reflect the spatio‐temporal pattern of task‐engagement, with alpha decrease signifying task‐involved regions and broadband increase temporally locking to specific task aspects, distributed over cortical sites. We report sites that only respond to stimulus presentation or to the decision report and, interestingly, sites that reflect the time‐on‐task. The latter predict the subject's reaction times on a trial‐by‐trial basis. A smaller subset of sites showed modulation with task condition. Taken together, alpha and broadband signals allow tracking of neuronal population dynamics across cortex on a fine temporal and spatial scale. Abstract : We examine the alpha‐band rhythm and broadband activity using intracranial recordings in a large cohort of patients with intractable epilepsy who performed a decision‐making task. We show that broadband activity, thought to be a proxy of local neuronal excitation, provides a readout of task‐specific information, such as task condition and reaction time. Critically, we find a negative correlation between broadband activity and the alpha rhythm across a widespread range of cortical areas, providing further evidence for the idea that alpha reflects a general gating mechanism, suppressing processing in task‐disengaged areas in favor of task‐engaged areas.